2015
DOI: 10.1371/journal.pone.0138716
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Mitochondrial DNA Copy Number Is Associated with Chronic Obstructive Pulmonary Disease

Abstract: BackgroundOxidative stress is known to be involved in the pathogenesis of chronic obstructive pulmonary disease (COPD). Evidence suggests that leukocytes mitochondria DNA (mtDNA) is susceptible to undergo mutations, insertions, or depletion in response to reactive oxidative stress (ROS). We hypothesize that mtDNA copy number is associated with the development of COPD.Methodology/Principal FindingsRelative mtDNA copy number was measured by a quantitative real-time PCR assay using DNA extracted from peripheral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
0
26
1
1
Order By: Relevance
“…In at least 1 study, exogenous mtDNA given intravascularly to rodents did not increase circulating mtDNA but increased u-mtDNA (26). U-mtDNA may also originate from renal cells, including glomerular or tubular epithelial cells (56), endothelial cells (44), and immune cells (6,12), as well as lung-derived cell sources (5)(6)(7)(8)(9)(10)(11)16) or muscle (65); further mechanistic studies are needed to identify the source of extracellular mtDNA in COPD. Whether u-mtDNA in COPD is a marker of disease or is pathogenic in itself remains to be determined.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…In at least 1 study, exogenous mtDNA given intravascularly to rodents did not increase circulating mtDNA but increased u-mtDNA (26). U-mtDNA may also originate from renal cells, including glomerular or tubular epithelial cells (56), endothelial cells (44), and immune cells (6,12), as well as lung-derived cell sources (5)(6)(7)(8)(9)(10)(11)16) or muscle (65); further mechanistic studies are needed to identify the source of extracellular mtDNA in COPD. Whether u-mtDNA in COPD is a marker of disease or is pathogenic in itself remains to be determined.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…One underlying biological mechanism that may provide insight into COPD pathogenesis and progression is mitochondrial dysfunction, which is consistently observed in cells derived from COPD subjects (5)(6)(7)(8)(9)(10)(11)(12)(13), as well as in experimental COPD models (11,14). Such mitochondrial dysfunction is associated with the leakage of mitochondrial DNA (mtDNA) (15)(16)(17)(18)(19), a mitochondrial derived danger-associated molecular pattern (mtDAMP) (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Although mtDNA copy numbers were not specifically assessed, the expression of mtDNA‐encoded COX2 was reduced, hinting to a reduction of mtDNA copy numbers. Accordingly, in patients with chronic obstructive pulmonary disease, a disorder associated with oxidative stress, leukocyte mtDNA copy numbers were lower than in healthy controls (Liu et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
“…AECOPD and PE are associated with a wide range of inflammatory cells, mediators and cytokine network components, including P-selectin (11,12), inflammatory cytokines (13,14) and leucocytes (15,16). Previous studies have indicated that eosinophilic airway inflammation is also associated with the development of severe AECOPD (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%